Highly efficient expansion of human CD4+CD25+ regulatory T cells for cellular immunotherapy in patients with graft-versus-host disease - Karakhanova, Svetlana; Munder, Markus; Schneider, Markus; Bonyhadi, Mark; Ho, Anthony Dick; Görner, Martin (Journal of immunotherapy, 2006)
CD4+CD25+ regulatory T cells (TREG) are engaged in the regulation of murine and human immune responses as well as graft-versus-host disease (GvHD) after allogeneic stem-cell transplantation. Despite their suppression of GvHD they do not impair graft-versus-tumor activity in the mouse, which makes TREG especially attractive candidates for cellular immunotherapy. TREG comprise only 5% to 10% of CD4+ T cells in peripheral blood and are naturally anergic, which prevented their use as therapeutic suppressor cells in the context of autoimmune or alloimmune reactions so far. We therefore developed an in vitro expansion protocol for human TREG, breaking their anergy with anti-CD3/anti-CD28-coupled paramagnetic beads and a combination of interleukin (IL)-2 and IL-15. Highly purified human TREG can be expanded 285-fold to 1000-fold within 20 days and keep their phenotype as well as all their suppressor functions even in the context of stimulation with mature allogeneic dendritic cells. However, we demonstrate that FoxP3 is not a reliable marker for human TREG as it is transiently inducible in CD4+CD25− cells upon activation with cytokines or via their T cell receptor. In addition, we successfully expanded CD4+CD25+ cells from patients after allogeneic stem-cell transplantation with or without GvHD and show that different suppressor functions might be lost independently, demonstrating that human TREG biology is likely more complicated than previously thought.
Die Pluszeichen im Titel sind hochgestellt
Gesehen am 09.11.2021